2014
DOI: 10.1080/10589759.2014.904313
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive testing and assessment of dynamic incompatibility between third-party piping and drain valve systems: an industrial case study

Abstract: This paper presents the outcome of an industrial case study that involved condition monitoring of piping system that showed signs of excess fatigue due to flow induced vibration. Due to operational requirements a novel non-destructive assessment stratagem was adopted using different vibration analysis techniquessuch as Experimental Modal Analysis (EMA) and Operating Deflection Shapes (ODS) -and complemented by visual inspection. Modal analysis performed near a drain valve showed a dynamic weakness problem (sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Contemporary ways for analyzing the industry objects of responsible purposes under exploitation consist in using non-destructive testing techniques [1] in various worldwide spheres of diagnostics of objects such as industrial and civil buildings, industrial piping systems, concrete bridges, nuclear power facilities [2][3][4][5][6][7] at al. Among these techniques the acoustic emission (AE) method takes the especial place when estimating the predestructive stages of exploited equipment material since AE method permits to detect growing defects being just the most dangerous [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contemporary ways for analyzing the industry objects of responsible purposes under exploitation consist in using non-destructive testing techniques [1] in various worldwide spheres of diagnostics of objects such as industrial and civil buildings, industrial piping systems, concrete bridges, nuclear power facilities [2][3][4][5][6][7] at al. Among these techniques the acoustic emission (AE) method takes the especial place when estimating the predestructive stages of exploited equipment material since AE method permits to detect growing defects being just the most dangerous [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Compactness of the operator of that system allows to represent its operator as the sum of finite-dimensional and infinitesimal ones. This fact permits to apply various numerical methods to solve the equations with compact operators and hence to solve input boundary value problem (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kong et al investigated flow induced vibration problem of in-service duplex stainless steel piping system as well as the third party piping and drain valve system of an offshore gas processing platform. Vibration analysis was performed in identifying structural dynamics issue of the third party piping and drain valve system and the results showed that there was design problem due to dissimilar stiffness and dynamic incompatibility between the supplied pipe and valve systems [13]. By combining both experimental and computational techniques, flow -induced vibrations and maximum dynamic stresses were calculated and the highest flow rate for the piping system to run under the allowable endurance stress limit and safe condition was forecasted [14].…”
Section: Introductionmentioning
confidence: 99%